Constructing Ethnicity and Identity of Bantawa Rai in Eastern Nepal (American Journal of Society and Law, 2025)
Ethnicity refers to the state of belonging to a particular ethnic group, generally recognized by both its members and others based on shared social and cultural characteristics. This study examines the processes involved in constructing and reconstructing ethnicity and identity among the Bantawa Rai in eastern Nepal. The theoretical discussion of this study is based on a constructivist approach, which provides a framework for understanding ethnicity as a dynamic and socially constructed phenomenon. The study relies on data collected from both primary and secondary sources. Secondary data has been gathered from various published and unpublished books, journals, articles, and research reports. Primary data was collected through in-depth interviews, observations, key informant interviews, and focused group discussions with cultural experts, teachers, ethnic activists, and political leaders. Informants were selected using a purposive sampling method to ensure relevant insights. The findings confirm that ethnicity is not a fixed entity but a dynamic and evolving process shaped by social and historical conditions. The construction of ethnicity and identity involves weakening of cultural differences and intensification of cultural homogeneity, influenced by geographical isolation, migration across ethnic boundaries, and increasing interactions with external groups. Additionally, increased mobility, social contact, and engagement with global forces, along with the decline of pre-capitalist economic structures and transformations in social organization, contribute to the evolving identity of the Bantawa Rai community.